Reduction in physical match performance at the start of the second half in elite soccer - Weston, M.; Batterham, A. M.; Castagna, C.; Portas, M. D.; Barnes, C. A.; Harley, J.; Lovell, R. J. (International Journal of Sports Physiology and Performance, 2011)
Purpose: Soccer referees` physical match performances at the start of the second half (46-60 min) were evaluated in relation to both the corresponding phase of the first half (0-15 min) and players` performances during the same match periods. Methods: Match analysis data were collected (Prozone, UK) from 12 soccer referees on 152 English Premier League matches during the 2008/09 soccer season. Physical match performance categories for referees and players were total distance, high-speed running distance (speed >5.5 m/s), and sprinting distance (>7.0 m/s). The referees` heart rate was recorded from the start of their warm-up to the end of the match. The referees` average distances (in meters) from the ball and fouls were also calculated. Results: No substantial differences were observed in duration (16:42 ± 2:35 vs 16:27 ± 1:00 min) or intensity (107 ± 11 vs 106 ± 14 beats/min) of the referees` preparation periods immediately before each half. Physical match performance was reduced during the initial phase of the second half when compared with the first half in both referees (effect sizes—standardized mean differences—0.19 to 0.73) and players (effect sizes 0.20 to 1.01). The degree of the decreased performance was consistent between referees and players for total distance (4.7 m), high-speed running (1.5 m), and sprinting (1.1 m). The referees were closer to the ball (effect size 0.52) during the opening phase the second half. Conclusion: Given the similarity in the referees` preparation periods, it may be that the reduced physical match performances observed in soccer referees during the opening stages of the second half are a consequence of a slower tempo of play.